Traditional Chinese medicine combined incense bead bracelet and preparation method thereof
Patent Information
- Application Number
- CN202611400188.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本发明的目的就是为了弥补现有技术的不足,提供了一种中药合香珠手串及其制备方法,香珠采用三层复合分层结构,内层设置梯度缓释药芯,区分芯核中心区与芯梯度外层圈层,搭配专用低温熔融交联粘合剂实现草本成分分级释放;中层为含复合益生菌孢子的微生物改性多孔缓冲层,可缓冲外力、分解草本大分子并稳定内部药效;外层构建双网络动态共价自修复汗液响应包膜,依托植物源交联剂形成可逆共价键,可自主修复表层细微损伤,并随人体汗液调节释香速率,各层经发酵形成无间隙分子互融界面,搭配配套梯度成型、冷冻造孔、浸涂覆膜、恒温发酵等制备工序,解决传统香珠释香周期短、易破损受潮、香气单一刺鼻等问题,兼具长效安神调理、耐磨损、体感自适应释香优势,适合规模化生产与日常养生佩戴
一、本发明通过设置三层差异化功能复合结构搭配梯度缓释药芯体系,实现中药香气与有效成分分层可控释放,内层区分中心与外层圈层两类中药粉体,结合专用低温熔融交联粘合剂,依靠内外粉体挥发油含量差异形成释放梯度,内部高稳定性药芯可长效留存安神类活性物质,外层易挥发芳香组分缓慢向外渗透,中间多孔缓冲层搭载复合益生菌孢子,互通微孔结构承接内层析出的活性成分,微生物菌群可温和分解中药大分子物质,弱化浓烈药味刺激感,同时缓冲外层包膜对内层芯体的挤压磨损,避免芯体碎裂漏粉,三层结构经恒温恒湿发酵形成分子互融界面,消除层间缝隙,阻断成分局部快速外泄问题,让香珠佩戴周期内香气输出均匀稳定,持续发挥草本舒缓调理作用。
Smart Images

Figure CN122997461A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of herbal aromatic health-preserving ornaments technology, specifically a Chinese herbal blended fragrance bead bracelet and its preparation method. Background Technology
[0002] As traditional herbal health culture continues to gain popularity, incense beads with aromatic conditioning effects are gradually becoming a mainstream category of daily health-wearing products. Modern consumers' demands for personal health accessories are no longer limited to simple decoration; they place greater emphasis on comprehensive performance aspects such as long-lasting fragrance release, gentle conditioning, and compatibility with the human body's wearing environment. In the development of existing incense products, various herbal medicinal materials, natural binders, and functionally modified excipients are widely used. The industry is also gradually exploring layered structural designs to optimize the fragrance release effect of the beads. Simultaneously, technologies such as microbial modification and dynamic cross-linked films are being used to improve the surface protective structure of the beads. Since the human hand continuously secretes sweat when wearing the beads for extended periods, fluctuations in external temperature and humidity, as well as daily friction and impacts, directly affect the beads. Therefore, the industry needs to simultaneously address multiple requirements, including stable release of internal medicinal effects, surface protection against wear and tear, and compatibility with the body's secretions. Various composite multilayer structures, functional microorganisms, and reversible cross-linked coating technologies provide a feasible research and development foundation for the iterative upgrade of these health-enhancing incense beads.
[0003] Traditional single-layer homogeneous scented beads lack a layered, slow-release design. All herbal ingredients are mixed and molded, resulting in a rapid and simultaneous evaporation of various aromatic and medicinal components. While the fragrance is strong in the short term, it dissipates quickly, and with prolonged wear, the effective ingredients are rapidly lost, making it difficult to achieve a long-lasting soothing and conditioning effect. The surface of conventional scented beads relies solely on a single layer of beeswax or ordinary plant-based adhesive, lacking a reversible self-repairing structure. Daily friction and impacts easily cause cracking, peeling, and damage, allowing moisture and sweat to penetrate the interior, causing the internal medicinal powder to become damp, clump, mold, and ineffective. Ordinary scented beads lack a transitional buffer structure; the inner medicinal core is directly bonded to the surface coating. During wear and compression, the inner medicinal core is easily broken and leaks powder. Furthermore, the lack of microbial modification components prevents the decomposition of large-molecule herbal active substances, resulting in a strong, pungent medicinal smell. Additionally, traditional scented beads lack the ability to release fragrance in response to sweat; the release rate is indistinguishable between dry and sweaty conditions, leading to a poor wearing experience. The simple adhesive bonding between layers easily causes delamination, further shortening the overall product lifespan. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a traditional Chinese medicine scented bead bracelet and its preparation method. The scented beads adopt a three-layer composite layered structure. The inner layer is set with a gradient slow-release medicine core, distinguishing the core core center area from the outer layer of the core gradient. It is used with a special low-temperature melt cross-linking adhesive to achieve graded release of herbal ingredients. The middle layer is a microbial modified porous buffer layer containing compound probiotic spores, which can buffer external forces, decompose herbal macromolecules, and stabilize the internal efficacy. The outer layer constructs a dual-network dynamic covalent self-repairing sweat-responsive membrane. It relies on plant-derived cross-linking agents to form reversible covalent bonds, which can autonomously repair minor surface damage and adjust the fragrance release rate according to human sweat. Each layer forms a gapless molecular interfusion interface through fermentation. With the matching gradient molding, freeze pore creation, dip coating, constant temperature fermentation and other preparation processes, it solves the problems of short fragrance release cycle, easy breakage and moisture absorption, and single pungent fragrance of traditional scented beads. It also has the advantages of long-lasting calming and conditioning, wear resistance, and body-adaptive fragrance release, making it suitable for large-scale production and daily health care wear.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: On one hand, a herbal scented bead bracelet is formed by stringing together multiple composite scented beads; each composite scented bead is arranged from the inside out as follows: an inner layer of gradient slow-release drug core, a middle layer of microbially modified porous transition buffer layer, and an outer layer of dynamic covalent self-repairing sweat-responsive coating; based on the total mass of a single composite scented bead, the inner layer of gradient slow-release drug core accounts for 60%-64% of the mass, the middle layer of microbially modified porous transition buffer layer accounts for 21%-25% of the mass, and the outer layer of dynamic covalent self-repairing sweat-responsive coating accounts for 13%-17% of the mass, and the sum of the mass percentages of the three is 100%; the inner layer of gradient slow-release drug core... The core comprises a core core central region and a core gradient outer layer covering the core core central region. The inner gradient sustained-release core contains traditional Chinese medicine raw materials and a styrax-amber low-temperature melt crosslinking adhesive. The middle layer of microbial modified porous transition buffer layer has a thickness of 0.5mm-0.7mm and is equipped with interconnected micropores. The middle microbial modified porous transition buffer layer contains freeze-dried compound probiotic spore powder. The outer layer of dynamic covalent self-repairing sweat-responsive membrane has a thickness of 0.2mm-0.3mm. This membrane has a dual network structure with interpenetrating physical polysaccharide crosslinking network and dynamic covalent crosslinking network. The outer layer of dynamic covalent self-repairing sweat-responsive membrane contains a plant-derived dynamic crosslinking agent.
[0006] Further, the weight ratio of the raw materials in the core core area is as follows: Poria cocos 20-24 parts, Agarwood 6-10 parts, Ziziphus jujuba var. spinosa 13-17 parts, Rehmannia glutinosa 8-12 parts, and Elm wood viscous powder 4-6 parts; after all the raw materials in the core core area are pulverized and passed through a 320-380 mesh sieve, the volatile oil content of the obtained powder is ≤1.5%; the weight ratio of the raw materials in the outer ring of the core gradient is as follows: Peppermint 4-8 parts, Eupatorium fortunei 5-9 parts, Clove 1-3 parts, Lavender 7-11 parts, and Styrax benzoin 2-4 parts; after all the raw materials in the outer ring of the core gradient are pulverized and passed through a 260-300 mesh sieve, the volatile oil content of the obtained powder is 3.5%-4.8%; the proportion of the Styrax benzoin-amber low-temperature melt crosslinking binder to the total mass of the inner gradient sustained-release drug core is 6%-10%.
[0007] Furthermore, the styrax-amber low-temperature melt crosslinking adhesive is made by mixing styrax resin fine powder and amber fine powder, with a mass ratio of styrax resin fine powder to amber fine powder of 1:1 to 2:1; the ambient temperature during the entire raw material crushing and processing of the core core central area and the core gradient outer layer is ≤40℃; after being pressed by pressure of 0.3MPa-0.4MPa, the core gradient outer layer is tightly bonded to the core core central area, with no gap between them.
[0008] Furthermore, the weight ratio of the basic components of the intermediate microbial modified porous transition buffer layer is as follows: 36-44 parts of fermented Chinese medicine residue ultrafine powder, 4-8 parts of konjac glucomannan, 10-14 parts of Poria cocos powder, and 2-4 parts of calcined calamine powder; freeze-dried compound probiotic spore powder is incorporated into the intermediate microbial modified porous transition buffer layer, and the freeze-dried compound probiotic spore powder accounts for 1%-3% of the total mass of the intermediate microbial modified porous transition buffer layer; the freeze-dried compound probiotic spore powder is composed of Bacillus subtilis spores and plant lactic acid bacteria spores.
[0009] Furthermore, the mass ratio of Bacillus subtilis spores to Lactobacillus plantarum spores in the freeze-dried compound probiotic spore powder is 1.0:1 to 1.2:1.
[0010] Furthermore, the weight ratio of the basic components of the outer dynamic covalent self-repairing sweat-responsive membrane is as follows: 16-20 parts okra mucilage concentrate, 5-9 parts locust bean gum, 1-3 parts beeswax microspheres, and 4-6 parts Atractylodes macrocephala extract; a plant-derived dynamic cross-linking agent is added to the outer dynamic covalent self-repairing sweat-responsive membrane, and the proportion of the plant-derived dynamic cross-linking agent to the total mass of the outer dynamic covalent self-repairing sweat-responsive membrane is 2%-5%; the plant-derived dynamic cross-linking agent is a curcumin-boric acid complex or proanthocyanidin extract.
[0011] Furthermore, the plant-derived dynamic crosslinking agent forms a dynamic covalent structure of borate ester bonds and Schiff base bonds with the polysaccharide molecules and locust bean gum molecules in the okra mucilage concentrate; the beeswax microspheres have a particle size distribution of 5μm-20μm and are uniformly dispersed within the physical polysaccharide crosslinking and dynamic covalent crosslinking interpenetrating double network structure of the outer dynamic covalent self-repairing sweat-responsive membrane.
[0012] Furthermore, the radial thickness of the outer ring of the core gradient covering the central region of the core is 0.8mm-1.2mm; the pore size distribution of the interconnected micropores inside the middle microbial modified porous transition buffer layer is 2μm-15μm; the three-layer structure of the inner gradient sustained-release drug core, the middle microbial modified porous transition buffer layer and the outer dynamic covalent self-repairing sweat response membrane forms a molecularly fused interface through constant temperature and humidity fermentation, and there is no physical separation gap between the three layers.
[0013] On the other hand, a method for preparing a traditional Chinese medicine incense bead bracelet, the specific steps of which are as follows: S1, Gradient Core Pre-forming and Shaping Process: Mix the raw materials in the central area of the core, combine with styrax-amber low-temperature melt crosslinking adhesive to press a solid core, let it stand at room temperature for 20-28 hours to set, then coat the outer layer of core gradient powder and press it with 0.3MPa-0.4MPa hydraulic pressure, and dry it at low temperature to adjust the core moisture content to 5%-7%; S2, middle buffer layer coating freezing pore-forming process: mix the middle layer base powder, mix in freeze-dried compound probiotic spore powder, add water to make paste and roll it onto the outer wall of the gradient core, freeze at -14℃~-10℃, and then vacuum dry at 30℃-34℃ to create pores. S3, self-healing coating dip-coating molding process: mix coating base raw materials with plant-derived dynamic crosslinking agent, heat water bath to 40℃-50℃ to obtain material solution, immerse beads in material solution for soaking and then lift them up, and hang them to air dry for 10-14 hours to form coating. S4, Interface solidification fermentation process: The molded incense beads are placed in a constant temperature and humidity sealed environment, with a temperature of 26℃-30℃ and a relative humidity of 60%-70%, and fermented continuously for 68-76 hours. S5, Finished Product Screening and Assembly Process: Select qualified incense beads and use woven thread and accessories to complete the bracelet assembly. Beneficial effects
[0014] Compared with existing technologies, the preparation method of this herbal incense bead bracelet has the following beneficial effects: I. This invention achieves layered and controllable release of the aroma and active ingredients of traditional Chinese medicine by setting up a three-layered differentiated functional composite structure combined with a gradient slow-release drug core system. The inner layer distinguishes between two types of traditional Chinese medicine powders: a central layer and an outer ring layer. Combined with a special low-temperature melt cross-linking adhesive, a release gradient is formed by the difference in volatile oil content between the inner and outer powders. The highly stable inner drug core can retain sedative active substances for a long time, while the volatile aromatic components of the outer layer slowly permeate outward. The middle porous buffer layer carries composite probiotic spores, and the interconnected microporous structure receives the active ingredients released from the inner layer. The microbial community can gently decompose the large molecules of traditional Chinese medicine, weakening the strong medicinal smell and irritating sensation. At the same time, it buffers the pressure and wear of the outer coating on the inner core, preventing the core from breaking and leaking powder. The three-layer structure forms a molecular interface through constant temperature and humidity fermentation, eliminating gaps between layers and blocking the problem of rapid local leakage of ingredients. This ensures that the aroma output is uniform and stable throughout the wearing period of the incense beads, continuously exerting the herbal soothing and conditioning effect.
[0015] II. This invention, by constructing a polysaccharide and dynamic covalent interpenetrating dual-network sweat-responsive coating, endows the fragrance beads with dual properties of self-repair and body-feel adaptation. The plant-derived cross-linking agent in the coating can form reversible dynamic covalent bonds with colloidal polysaccharides, allowing the micro-cracks caused by daily bumps and friction to close autonomously, extending the complete lifespan of the fragrance beads. The beeswax microspheres dispersed inside the coating slowly swell upon contact with human sweat, regulating the opening and closing of the coating pores. When the wearer sweats, the pores expand moderately to accelerate the release of fragrance, while in dry environments, the pores contract to lock in the medicinal fragrance, achieving intelligent adjustment of the fragrance release rate according to the body's surface condition. The porous buffer layer, created using a low-temperature freezing pore-forming process, retains the activity of probiotics. The coating isolates the bacterial community from external dust and moisture. The three-layer structure works together to block external temperature and humidity, as well as sweat impurities, from directly contacting the medicinal core, significantly reducing the probability of the Chinese herbal raw materials becoming damp, deteriorating, or losing their effectiveness through volatilization, while taking into account the wearing feel, appearance integrity, and long-lasting fragrance release effect.
[0016] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.
[0018] Figure 1 This is a flowchart illustrating a method for preparing a traditional Chinese medicine incense bead bracelet. Detailed Implementation
[0019] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below. Example
[0020] A multi-layer gradient sustained-release traditional Chinese medicine incense bead bracelet preparation process, the specific steps of which are as follows: Figure 1 As shown.
[0021] S1, Gradient core pre-forming and shaping process: The core core was prepared using the middle weight proportions of the raw materials from the central region: 22 parts Poria cocos, 8 parts Agarwood, 15 parts Ziziphus jujuba var. spinosa, 10 parts Rehmannia glutinosa, and 5 parts Elm wood adhesive powder. All raw materials were put into a closed low-temperature pulverizing equipment for ultrafine pulverization. The ambient temperature was controlled below 40 degrees Celsius throughout the pulverization process. After pulverization, all powders were sieved through a 350-mesh sieve. The sieved powders were allowed to stand naturally to balance the moisture content, and samples were taken to test the volatile oil content inside the powders. Styrax resin powder and amber powder were mixed evenly at a mass ratio of 1.5:1 to obtain a styrax-amber low-temperature melt crosslinking binder, which accounted for 8% of the total mass of the inner gradient slow-release core. The core core powder and binder were put into a three-dimensional mixing device and stirred continuously for 40 minutes. After being mixed evenly, the mixture was sent to a spherical mold and statically pressed at room temperature to obtain a solid spherical core. The formed core was placed in a light-proof and dust-free space and left to stand at room temperature for 24 hours to complete the shaping.
[0022] The raw materials for the outer ring of the core gradient were taken from the middle weight range: 6 parts peppermint, 7 parts agastache, 2 parts clove, 9 parts lavender, and 3 parts styrax gum. The grinding and processing temperature was controlled below 40 degrees Celsius. After grinding, the powder was sieved through a 280-mesh sieve. After the powder was allowed to stand to balance the moisture content, the volatile oil content was tested. The sieved ring powder was evenly spread and wrapped around the outer surface of the solid core. It was then fed into a hydraulic forming equipment and pressed at a constant speed under a pressure of 0.35 MPa. After pressing, the radial thickness of the outer ring of the core gradient was maintained at 1 mm. The central area of the core core and the outer ring of the core gradient were completely bonded together, with no gaps at the contact surface. After pressing, the composite core was sent to a low-temperature hot air drying equipment for continuous drying for 6 hours. The internal moisture content of the core was monitored in real time, and the moisture content of the core was finally stabilized at 6%.
[0023] S2, intermediate buffer layer coating cryogenic pore-forming process: The middle layer base components are as follows by weight: 40 parts fermented Chinese herbal medicine residue ultrafine powder, 6 parts konjac glucomannan, 12 parts Poria cocos powder, and 3 parts calcined calamine powder. The freeze-dried compound probiotic spore powder is a mixture of Bacillus subtilis spores and plant lactic acid bacteria spores at a mass ratio of 1.1:1, and the spore powder accounts for 2% of the total mass of the middle layer materials. The middle layer base powder and the freeze-dried compound probiotic spore powder are added to a dry powder mixing device and stirred for 30 minutes. After mixing evenly, purified water is added in small amounts in batches and stirred at low speed for 25 minutes each time to obtain a viscous paste without particles. The paste is completely coated onto the outer wall of the gradient core using a roller coating process, with the coating thickness maintained at a stable 0.6 mm. After coating, the semi-finished product is quickly transferred to a low-temperature freezing chamber and frozen at -12 degrees Celsius for 6 hours. After the freezing process, it is sent to a vacuum drying equipment and dried at a constant temperature of 32 degrees Celsius for 8 hours to complete the pore formation. After drying, a large number of interconnected micropores are generated inside the middle layer, with the micropore size distribution range from 2 μm to 15 μm.
[0024] S3, Self-healing coating dip-coating molding process: The basic components of the outer dynamic covalent self-repairing sweat-responsive coating are as follows (by weight): 18 parts okra mucilage concentrate, 7 parts locust bean gum, 2 parts beeswax microspheres, and 5 parts Atractylodes macrocephala extract. Proanthocyanidin extract was selected as the plant-derived dynamic cross-linking agent, accounting for 3.5% of the total mass of the outer coating. The beeswax microspheres have a particle size distribution ranging from 5μm to 20μm. The okra mucilage concentrate, locust bean gum, and Atractylodes macrocephala extract were added to a constant-temperature water bath and stirred at 45°C for 1 hour. Then, beeswax microspheres and proanthocyanidin extract were added sequentially, and stirring continued at a constant temperature for another 2 hours to obtain a homogeneous, clumpy-free coating solution. The beads coated with the middle buffer layer were completely immersed in the solution and allowed to stand for 10 minutes. The beads were then lifted vertically upwards at a uniform speed and suspended in a dust-free, temperature-controlled, ventilated chamber to air dry naturally for 12 hours, ultimately forming a continuous and complete coating with a thickness of 0.25mm. Plant-derived dynamic cross-linking agents react with okra mucilage concentrate and locust bean gum to generate borate ester bonds and Schiff base bonds, constructing a double network structure of interpenetrating physical polysaccharide cross-linking network and dynamic covalent cross-linking network. Beeswax microspheres are uniformly dispersed inside the double network structure, without local aggregation.
[0025] S4, Interface solidification fermentation process: Three layers of composite semi-finished fragrance beads were neatly laid out inside a sealed, temperature- and humidity-controlled fermentation chamber. The chamber maintained an internal temperature of 28 degrees Celsius and a relative humidity of 65%, ensuring complete airtightness and continuous constant temperature and humidity fermentation for 72 hours. After fermentation, several beads were randomly selected and longitudinally cut to observe the cross-section. The three-layer structure formed a continuous molecular interface, with no visible physical gaps between the layers. The mass distribution of the three layers in a single composite fragrance bead was as follows: inner layer gradient slow-release core 62%, middle layer microbial modified porous transition buffer layer 23%, and outer layer dynamic covalent self-repairing sweat-responsive coating 15%. The total mass of the three layers added together equaled 100.
[0026] S5, Finished product screening and assembly process: After the fermentation process is completed, all the incense beads are sorted. Defective beads with deformed spheres, cracked surfaces, broken membranes, interlayer separation, or dimensional deviations are removed. Only well-formed, intact, and defect-free composite incense beads are retained. These are then hand-strung together using cotton wax weaving thread and natural jade spacer beads, resulting in a complete herbal incense bead bracelet. Example
[0027] Characterization of the microstructure of multilayer composite fragrance beads and feasibility verification of sustained-release self-healing microbial activity.
[0028] Microscopic characterization of the three-layer composite structure: The finished fragrance beads prepared in Example 1 were longitudinally sectioned, and their microstructure was observed using a scanning electron microscope. At 500x magnification, three independent layers were clearly distinguishable. The inner gradient sustained-release core consists of a core center and an outer gradient layer. The core center has tightly compacted powder with few internal pores, while the outer gradient layer has fine powder gaps and uniformly distributed volatile oil storage channels. The middle microbial modified porous transition buffer layer has a cross-section filled with continuous, interconnected micropores ranging from 2μm to 15μm in diameter. Freeze-dried compound probiotic spores are completely attached to the inner walls of the micropores without large-scale detachment. The outer dynamic covalent self-repairing sweat-responsive membrane exhibits a continuous network structure, with polysaccharide physical cross-linking networks and dynamic covalent cross-linking networks interwoven. Beeswax microspheres with particle sizes ranging from 5μm to 20μm are uniformly embedded in the network gaps.
[0029] Ten beads were randomly selected using a high-precision micrometer and their thickness was repeatedly measured. The average thickness of the middle buffer layer was 0.6 mm, the average thickness of the outer coating was 0.25 mm, and the average radial thickness of the core gradient outer ring was 1 mm.
[0030] Gradient-release fragrance retention performance verification: Two parallel sample groups were set up. The control group consisted of single-layer homogeneous fragrance beads with the same proportion of Chinese herbal raw materials, while the experimental group consisted of three-layer gradient composite fragrance beads as described in this embodiment. The total mass of each bead in both groups was kept exactly the same. Both groups of samples were placed in a sealed container in a constant temperature water bath at 37 degrees Celsius. The volatile oil in the container was collected and weighed at fixed times every day for 15 consecutive days, and the total amount released was recorded. The single-layer homogeneous fragrance beads released a large amount of volatile oil in the first 3 days, and the amount of volatile oil released decreased continuously in the following 12 days, with the aroma fading rapidly. The three-layer gradient composite fragrance beads released volatile oil at a slow and stable pace. In the first 5 days, some volatile oil was released slowly. From the 6th to the 12th day, the volatile oil was released at a uniform and stable rate. From the 13th to the 15th day, the remaining volatile oil was released slowly. The problem of a large amount of volatile oil released in the early stage and no aroma released in the later stage was not observed throughout the process.
[0031] Verification of the membrane's sweat response and self-healing properties: Artificial sweat, formulated according to the standard components of human sweat, is evenly sprayed onto the surface of the scented bead coating. Upon contact with the sweat, the dynamic covalent bonds within the coating reversibly dissociate, causing a slight expansion of the micropores and a simultaneous increase in the release rate of the volatile oil from the internal core. The sweat is then wiped away with a clean, soft cloth. As the moisture evaporates slowly, the dynamic covalent bonds recombine, and the pores close, locking in the internal volatile oil. Fine scratches (0.1 mm wide) are then created on the coating surface using fine sandpaper. The beads with these scratches are placed at room temperature for 24 hours. The residual sweat on the coating surface continues to induce the dynamic covalent bonds to crosslink again, gradually closing the scratches. After 24 hours, there are no obvious signs of damage to the coating surface.
[0032] Verification of the activity of freeze-dried compound probiotics in the middle layer: 1g of the middle buffer layer powder was peeled off, dissolved in 9mL of sterile physiological saline by thorough shaking, serially diluted, and then spread onto agar plates. The plates were incubated at 30°C for 24 hours for viable cell counting. After the entire cryopreservation and constant-temperature fermentation process, the combined viable cell retention rate of Bacillus subtilis spores and Lactobacillus plantarum spores was high, indicating that the microorganisms stably adhered to the interior of the middle micropores and continuously exerted a buffering and antibacterial effect. Example
[0033] Optimization test of raw material ratio range for each layer.
[0034] In this embodiment, multiple parallel samples were prepared by adjusting the mass ratio of the three-layer materials, the proportion of probiotics added in the middle layer, and the proportion of cross-linking agent added in the outer layer. All other preparation process parameters were kept uniform, and the total mass of each sample was kept at the same value. After all processing and testing were completed, the test data were summarized and obtained as shown in the table below.
[0035] Table 1. Comparison of comprehensive performance of samples with different raw material ratios: Sample 1 58% 25% 17% 2% 3.5% generally Poor medium Sample 2 62% 23% 15% 2% 3.5% excellent excellent excellent Sample 3 66% 21% 13% 2% 3.5% good generally Poor Sample 4 62% 23% 15% 0.5% 3.5% excellent excellent excellent Sample 5 62% 23% 15% 4% 3.5% Poor good medium Sample 6 62% 23% 15% 2% 1% excellent generally medium Sample 7 62% 23% 15% 2% 6% Poor excellent Poor Analysis of material mass distribution ratio data in three layers: Sample 1 had a low proportion of inner layer material, resulting in insufficient total reserves of volatile oils from the Chinese herbal medicine within the bead. During the 7-day continuous release, the aroma decayed rapidly, and the daily release of volatile oils fluctuated significantly. Sample 3 had a high proportion of inner layer material, leading to a thinner outer coating, reduced surface abrasion resistance, and easy surface damage after slight compression. The bead exhibited poor compressive strength. Sample 2 showed a balanced distribution of materials across the three layers, exhibited no cracking or deformation during bead formation, had minimal fluctuations in daily volatile oil release, and demonstrated the best compressive durability among all samples.
[0036] Analysis of data on the proportion of freeze-dried compound probiotic spore powder added in the middle layer: Sample 4 had a low spore powder content, resulting in insufficient effective microorganisms in the middle layer and weak antibacterial effect during wear. Sample 5 had a high spore powder content, leading to decreased adhesion of the middle layer paste, easy flaking off of the surface layer after freeze-drying, and a poor bead integrity rating. Sample 2 had a moderate spore powder content, stable paste flowability during mixing and processing, intact microporous structure in the middle layer after drying, and sufficient and stable microbial activity.
[0037] Analysis of data on the proportion of plant-derived dynamic cross-linking agents added to the outer layer: Sample 6 had a low crosslinking agent content, resulting in a sparse double crosslinking network structure. The porosity adjustment after the coating came into contact with sweat was limited, and the uniformity of volatile oil release after 7 days was only average. Sample 7 had a high crosslinking agent content, resulting in a hard and brittle texture after coating curing, easily developing through-cracks from minor impacts, and exhibiting poor compressive strength. Sample 2 had a moderate crosslinking agent content, a stable polysaccharide and dynamic covalent double network structure, sensitive sweat response, and a stable and long-lasting self-healing effect on coating scratches. Example
[0038] Optimization experiments were conducted on key process parameters for preparation.
[0039] In this embodiment, multiple sets of samples were prepared by sequentially adjusting four process parameters: freezing temperature, vacuum drying temperature, layering and pressing pressure, and core powder sieving mesh size. The raw material ratio remained constant throughout the entire process. After completing the entire preparation process, multiple indicators were tested, and the test data are summarized in the table below.
[0040] Table 2 Comparison of sample performance with different preparation process parameters: Sample A -8℃ 32℃ 0.35MPa 350 mesh Poor excellent 6 days Sample B -12℃ 32℃ 0.35MPa 350 mesh excellent excellent 15 days Sample C -16℃ 32℃ 0.35MPa 350 mesh generally excellent 12 days Sample D -12℃ 28℃ 0.35MPa 350 mesh good excellent 11 days Sample E -12℃ 36℃ 0.35MPa 350 mesh generally excellent 13 days Sample F -12℃ 32℃ 0.25MPa 350 mesh excellent Poor 5 days Sample G -12℃ 32℃ 0.45MPa 350 mesh excellent excellent 8 days Sample H -12℃ 32℃ 0.35MPa 300 mesh excellent excellent 7 days Sample I -12℃ 32℃ 0.35MPa 400 mesh excellent excellent 9 days Analysis of temperature data for freeze-drying and vacuum drying: Sample A had a high freezing temperature, preventing sufficient formation of uniform ice crystals within the paste. After molding, the number of micropores in the middle layer was sparse, resulting in insufficient aroma penetration channels and a stable release of volatile oils for only 6 days. Sample C had a low freezing temperature, leading to excessively large ice crystals. After drying, fine, interconnected cracks appeared within the middle layer, resulting in a generally poor micropore integrity rating. Sample D had a low drying temperature, resulting in slow water sublimation and incomplete micropore formation. Sample E had a high drying temperature, causing rapid hardening of the bead surface and blocking internal aroma penetration channels. Sample B, frozen at -12℃ and vacuum-dried at 32℃, exhibited a uniform and complete distribution of interconnected micropores in the middle layer, allowing for a stable release of volatile oils for 15 days.
[0041] Analysis of core gradient outer layer lamination pressure data: Sample F had a low compression pressure, resulting in micron-sized gaps between the outer layer of the core gradient and the central core area. This caused volatile oils to rapidly leak out through these gaps, resulting in a stable release period of only 5 days. Sample G had a high compression pressure, leading to excessive compaction of the powder layers and complete blockage of internal pores. This obstructed the outward permeation of volatile oils, shortening the stable release period to 8 days. Sample B, after compression at 0.35 MPa, exhibited no gaps between layers, retained moderate micropores within the powder, and maintained unobstructed aroma release pathways throughout.
[0042] Analysis of powder sieving mesh size data in the core center area: Sample H has a powder sieve mesh value that is too small, resulting in larger powder particle size and excessive porosity within the core, leading to rapid initial release of volatile oil. Sample I has a powder sieve mesh value that is too large, resulting in overly fine powder particles and a dense core with no slow-release channels after pressing. Sample B has a 350-mesh sieve and moderately sized powder particles, enabling a long-term, stable, and uniform release of volatile oil. Example
[0043] Specialized test on the performance of wearing and using traditional Chinese medicine incense bead bracelets.
[0044] In this embodiment, multiple sets of samples with different structures and ratios were prepared, and four wearing performance tests were uniformly carried out: long-lasting fragrance duration, sweat environment adaptability, mechanical friction durability, and microbial antibacterial properties. The raw material ratio values of all samples were within the set range, and the processing technology maintained a uniform standard. All test results are summarized in the table below.
[0045] Table 3 Comparison of wearing performance of different samples: Sample 1: Single-layer homogeneous fragrance beads 30 days No sweat response adjustment function Severe wear 3.2 Sample 2 Three-layer gradient composite fragrance beads 90 days Automatic pore adjustment prevents powder shedding Slight wear 12.6 Sample 3: Middle layer low spore powder sample 68 days Automatic pore adjustment prevents powder shedding Slight wear 5.8 Sample 4, outer layer low crosslinking agent sample 75 days The pore adjustment range is too small. Moderate wear 12.4 Five-layer low-pressure synthetic specimen 52 days Automatic pore adjustment results in slight powder shedding. Moderate wear 12.5 Long-lasting fragrance duration data analysis: Sample 1, with its single-layer homogeneous structure lacking multi-layer gradient slow-release stratification, exhibited no long-lasting volatile oil retention structure, and its aroma essentially dissipated completely after 30 days. Sample 2, with its complete three-layer gradient stratification structure, retained volatile oil in layers; its aroma concentration remained stable with no significant decay for the first 60 days, and a light, soothing herbal aroma was still perceptible after 90 days. Sample 3 had a low proportion of spore powder added to the middle layer, reducing the microporous buffering capacity and shortening the total aroma retention days to 68 days. Sample 4 had an insufficient proportion of cross-linking agent, weakening the coating and aroma-locking ability, resulting in a total aroma retention of 75 days. Sample 5 had insufficient layer-by-layer compression pressure, causing continuous loss of volatile oil due to interlayer gaps, and its aroma only noticeably faded after 52 days.
[0046] Analysis of sweat compatibility and friction durability performance data: Sample 1, a single-layer scented bead, lacks a self-healing sweat-responsive coating. Upon contact with human sweat, the surface softens and peels off, exhibiting severe wear after 1000 cycles of friction. Sample 2, with its dual-network structure coating, reversibly adjusts pore opening and closing according to sweat content. Friction produces only minor scratches, which automatically repair themselves after resting, showing only slight wear after thousands of cycles. Sample 4 has insufficient cross-linking agent, resulting in low overall cross-linking network strength and moderate wear after friction. Sample 5 exhibits minute gaps between layers, causing slight powdering after sweat seeps into these gaps.
[0047] Analysis of microbial antibacterial performance data: Sample 1 lacked a middle probiotic buffer layer, and its average inhibition zone diameter was only 3.2 mm, failing to effectively inhibit pathogenic bacteria on the skin surface of the hands. Sample 2 had an appropriate proportion of spore powder, and its average inhibition zone diameter was 12.6 mm, demonstrating outstanding antibacterial effect. Sample 3 had an insufficient proportion of spore powder, resulting in a reduced inhibition zone diameter of 5.8 mm and a significant decrease in antibacterial ability. Samples 4 and 5 had normal probiotic proportions, and their inhibition zone sizes were similar to those of Sample 2.
[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A herbal scented bead bracelet, characterized in that it is formed by stringing together multiple composite scented beads; each composite scented bead is provided with, from the inside out, an inner gradient slow-release drug core, a middle microbial modified porous transition buffer layer, and an outer dynamic covalent self-repairing sweat-responsive coating; based on the total mass of a single composite scented bead, the inner gradient slow-release drug core accounts for 60%-64% of the mass, the middle microbial modified porous transition buffer layer accounts for 21%-25% of the mass, and the outer dynamic covalent self-repairing sweat-responsive coating accounts for 13%-17% of the mass, and the sum of the mass percentages of the three is 100%; the inner gradient slow-release drug core includes a core central area and a coating. The core core is covered by an outer ring of gradient layers, and the inner gradient sustained-release core contains traditional Chinese medicine raw materials and a styrax-amber low-temperature melt crosslinking adhesive; the middle layer of microbial modified porous transition buffer layer has a thickness of 0.5mm-0.7mm, and interconnected micropores are set in this layer, and the middle layer of microbial modified porous transition buffer layer contains freeze-dried compound probiotic spore powder; the outer layer of dynamic covalent self-repairing sweat-responsive membrane has a thickness of 0.2mm-0.3mm, and this membrane has a dual network structure with interpenetrating physical polysaccharide crosslinking network and dynamic covalent crosslinking network, and the outer layer of dynamic covalent self-repairing sweat-responsive membrane contains plant-derived dynamic crosslinking agent.
2. The herbal incense bead bracelet according to claim 1, characterized in that, The weight proportions of the raw materials in the core core area are as follows: 20-24 parts Poria cocos, 6-10 parts Agarwood, 13-17 parts Ziziphus jujuba var. spinosa, 8-12 parts Rehmannia glutinosa, and 4-6 parts Elm wood viscous powder. After all the raw materials in the core core area are pulverized, they are passed through a 320-380 mesh sieve, and the volatile oil content of the resulting powder is ≤1.5%. The weight proportions of the raw materials in the outer ring of the core gradient are as follows: 4-8 parts Peppermint, 5-9 parts Eupatorium fortunei, 1-3 parts Clove, 7-11 parts Lavender, and 2-4 parts Styrax benzoin. After all the raw materials in the outer ring of the core gradient are pulverized, they are passed through a 260-300 mesh sieve, and the volatile oil content of the resulting powder is 3.5%-4.8%. The proportion of the Styrax benzoin-amber low-temperature melt crosslinking binder to the total mass of the inner gradient sustained-release drug core is 6%-10%.
3. A traditional Chinese medicine incense bead bracelet according to claim 2, characterized in that, The styrax-amber low-temperature melt crosslinking adhesive is made by mixing styrax resin fine powder and amber fine powder, with a mass ratio of styrax resin fine powder to amber fine powder of 1:1 to 2:1; the ambient temperature during the entire raw material crushing and processing of the core core central area and the core gradient outer layer is ≤40℃; after being pressed by pressure of 0.3MPa-0.4MPa, the core gradient outer layer is tightly bonded to the core core central area, with no gap between them.
4. A traditional Chinese medicine incense bead bracelet according to claim 1, characterized in that, The weight ratio of the basic components of the middle layer microbial modified porous transition buffer layer is as follows: 36-44 parts of fermented Chinese herbal medicine residue ultrafine powder, 4-8 parts of konjac glucomannan, 10-14 parts of Poria cocos powder, and 2-4 parts of calcined calamine powder; freeze-dried compound probiotic spore powder is incorporated into the middle layer microbial modified porous transition buffer layer, and the freeze-dried compound probiotic spore powder accounts for 1%-3% of the total mass of the middle layer microbial modified porous transition buffer layer; the freeze-dried compound probiotic spore powder is composed of Bacillus subtilis spores and plant lactic acid bacteria spores.
5. A traditional Chinese medicine incense bead bracelet according to claim 4, characterized in that, The mass ratio of Bacillus subtilis spores to Lactobacillus plantarum spores in the freeze-dried compound probiotic spore powder is 1.0:1 to 1.2:
1.
6. A traditional Chinese medicine incense bead bracelet according to claim 1, characterized in that, The weight ratio of the basic components of the outer dynamic covalent self-repairing sweat-responsive membrane is as follows: 16-20 parts okra mucilage concentrate, 5-9 parts locust bean gum, 1-3 parts beeswax microspheres, and 4-6 parts Atractylodes macrocephala extract. A plant-derived dynamic cross-linking agent is added to the outer dynamic covalent self-repairing sweat-responsive membrane, and the proportion of the plant-derived dynamic cross-linking agent to the total mass of the outer dynamic covalent self-repairing sweat-responsive membrane is 2%-5%. The plant-derived dynamic cross-linking agent is a curcumin-boric acid complex or proanthocyanidin extract.
7. A traditional Chinese medicine incense bead bracelet according to claim 6, characterized in that, The plant-derived dynamic crosslinking agent forms a dynamic covalent structure of borate ester bonds and Schiff base bonds with the polysaccharide molecules and locust bean gum molecules in the okra mucilage concentrate; the beeswax microspheres have a particle size distribution of 5μm-20μm and are uniformly dispersed in the physical polysaccharide crosslinking and dynamic covalent crosslinking interpenetrating double network structure of the outer dynamic covalent self-repairing sweat-responsive membrane.
8. A traditional Chinese medicine incense bead bracelet according to claim 1, characterized in that, The outer layer of the core gradient envelops the central region of the core with a radial thickness of 0.8mm-1.2mm; the interconnected micropores in the middle layer of the microbial modified porous transition buffer layer have a pore size distribution of 2μm-15μm; the three-layer structure of the inner gradient sustained-release drug core, the middle layer of the microbial modified porous transition buffer layer, and the outer layer of the dynamic covalent self-repairing sweat-responsive membrane forms a molecularly fused interface through constant temperature and humidity fermentation, and there are no physical separation gaps between the three layers.
9. A method for preparing a traditional Chinese medicine blended incense bead bracelet, the method being applicable to the traditional Chinese medicine blended incense bead bracelet described in any one of claims 1-8, characterized in that, The specific steps of this preparation method are as follows: S1, Gradient Core Pre-forming and Shaping Process: Mix the raw materials in the central area of the core, combine with styrax-amber low-temperature melt crosslinking adhesive to press a solid core, let it stand at room temperature for 20-28 hours to set, then coat the outer layer of core gradient powder and press it with 0.3MPa-0.4MPa hydraulic pressure, and dry it at low temperature to adjust the core moisture content to 5%-7%; S2, middle buffer layer coating freezing pore-forming process: mix the middle layer base powder, mix in freeze-dried compound probiotic spore powder, add water to make paste and roll it onto the outer wall of the gradient core, freeze at -14℃~-10℃, and then vacuum dry at 30℃-34℃ to create pores. S3, self-healing coating dip-coating molding process: mix coating base raw materials with plant-derived dynamic crosslinking agent, heat water bath to 40℃-50℃ to obtain material solution, immerse beads in material solution for soaking and then lift them up, and hang them to air dry for 10-14 hours to form coating. S4, Interface solidification fermentation process: The molded incense beads are placed in a constant temperature and humidity sealed environment, with a temperature of 26℃-30℃ and a relative humidity of 60%-70%, and fermented continuously for 68-76 hours. S5, Finished Product Screening and Assembly Process: Select qualified incense beads and use woven thread and accessories to complete the bracelet assembly.
